Analisis Perbuatan Melawan Hukum Terkait Kasus Penyerobotan Tanah dalam Putusan Nomor 16/PDT/2022/PT BTN - Andryawan Andryawan; Ririn Khairunisa; Salma Setiawati; Diva Khairunisa; Ellina Dewi; Kezia Estevania Christabel Eliezer (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Land encroachment is a problem that often occurs in social environments, as it falls under the category of unlawful acts, as stated in Article 1365 of the Civil Code, which states that "Any act that violates the law and causes harm to another person obliges the perpetrator to compensate for the loss due to their fault." Land encroachment can be categorised as an unlawful act because it meets the requirements of an unlawful act, namely, it must be an act that constitutes an unlawful act, fault, the loss caused, and a causal relationship between the act and the loss. The objective of the research in this case study is to identify the decision of the Banten High Court with Number 16/PDT/2022/PT Banten and to discuss the legal implications that can be applied to this case. The connection with land ownership encroachment in this article also analyses the important role of documents as proof of land ownership rights and the importance of verifying the validity of documents to possess land rights.